INTERACTIVE MEDIA TO LEARN IDENTIFYING PATTERNS AND CALCULATING GEOMETRY OBJECTS ( CASE STUDY: TK ABA SURYA MELATI, YOGYAKARTA) - Dwi Nugraheny; Arry Dwi Setiawan (Institut Teknologi Dirgantara Adisutjipto, 2018)
Interactive learning media is the media more effectively so that the user can feel the learn more practical yet fun and stimulating for users desirous of learning. The pattern is the process of recognizing an object based on data that already exists to distinguish various patterns with different size and geometry of each pattern is obtained. The purpose of this thesis was to design an interesting learning media and interactive, in particular to facilitate the child TK Aba Surya Melati get to learn identifying pattern and calculating geometry objects. Based on testing performed, the results obtained to learn identifying pattern 80% and calculating geometry objects is 65%.